Costs, benefits, and cost-benefit of Collaborative Assessment and Management of Suicidality versus enhanced treatment as usual. - Phoebe K McCutchan; Brian T Yates; David A Jobes; Amanda H Kerbrat; Katherine Anne Comtois (PLoS ONE)
Suicide rates have been steadily increasing in both the U.S. general population and military, with significant psychological and economic consequences. The purpose of the current study was to examine the economic costs and cost-benefit of the suicide-focused Collaborative Assessment and Management of Suicidality (CAMS) intervention versus enhanced treatment as usual (ETAU) in an active duty military sample using data from a recent randomized controlled trial of CAMS versus ETAU. The full intent-to-treat sample included 148 participants (mean age 26.8 years ± 5.9 SD years, 80% male, 53% White). Using a micro-costing approach, the cost of each condition was calculated at the individual level from a healthcare system perspective. Benefits were estimated at the individual level as cost savings in past-year healthcare expenditures based on direct care reimbursement rates. Cost-benefit was examined in the form of cost-benefit ratios and net benefit. Total costs, benefits, cost-benefit ratios, and net benefit were calculated and analyzed using general linear mixed modeling on multiply imputed datasets. Results indicated that treatment costs did not differ significantly between conditions; however, CAMS was found to produce significantly greater benefit in the form of decreased healthcare expenditures at 6-month follow-up. CAMS also demonstrated significantly greater cost-benefit ratios (i.e., benefit per dollar spent on treatment) and net-benefit (i.e., total benefit less the cost of treatment) at 12-month follow-up. The current study suggests that beyond its clinical effectiveness, CAMS may also convey potential economic advantages over usual care for the treatment of suicidal active duty service members. Our findings demonstrate cost savings in the form of reduced healthcare expenditures, which theoretically represent resources that can be reallocated toward other healthcare system needs, and thus lend support toward the overall value of CAMS.